2014
DOI: 10.1016/j.mex.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

New closed tube loop mediated isothermal amplification assay for prevention of product cross-contamination

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 14 publications
1
70
0
5
Order By: Relevance
“…LAMP has been designed for various pathogens and has also been developed for detection of Arcobacter spp. Karthik et al 2014b;Wang et al 2014). Results showed that the developed LAMP assay was more sensitive than the other molecular assays like multiplex PCR and conventional PCR that were compared in the study (Wang et al 2014).…”
Section: Detection Of Arcobacter Spp By Molecular Methodsmentioning
confidence: 89%
“…LAMP has been designed for various pathogens and has also been developed for detection of Arcobacter spp. Karthik et al 2014b;Wang et al 2014). Results showed that the developed LAMP assay was more sensitive than the other molecular assays like multiplex PCR and conventional PCR that were compared in the study (Wang et al 2014).…”
Section: Detection Of Arcobacter Spp By Molecular Methodsmentioning
confidence: 89%
“…LAMP assay has the intrinsic property of product carry over contamination hence a novel closed tube LAMP assay was also developed for detection of Brucella spp. (Karthik et al, 2014b). LAMP assay for specific diagnosis of B. abortus was also developed which was 100 fold more sensitive than the commonly employed PCR (Karthik et al, 2014c).…”
Section: Serological Tests Like Rose Bengal Plate Test (Rbpt) Standamentioning
confidence: 99%
“…False positives observed in our study, could also stem from cross-contamination between positive and negative samples in the final stage of the test run. It was shown by Karthik et al (2014) that it is possible to contaminate working area when tubes are opened after isothermal amplification for addition of fluorescent dye. Replacing SYBR Green with calcein or hydroxyl methyl blue added before reaction (Goto et al 2009) could eliminate this problem.…”
Section: Resultsmentioning
confidence: 99%